Understanding, recognizing, and sharing energy poverty knowledge and gaps in Latin America and the Caribbean – because conocer es resolver - Thomson, Harriet (2022)
Despite specific historical, geographical, sociodemographic, and infrastructural conditions that in combination could produce very high levels of energy vulnerability, there are significant and enduring knowledge gaps concerning energy poverty in Latin America and the Caribbean. Bringing together a multi-disciplinary and multi-national team, we focus on establishing the state-of-the-art in knowledge and policy for 5 diverse case studies - Argentina, Brazil, Colombia, Cuba, and Mexico - as well as for the wider region. Our article has three specific aims: to establish the range of approaches used to research energy poverty across the region; to examine national and supranational policy obligations; and to lay the framework for new research and policy agendas. In combination, our extensive academic and grey literature reviews, and accompanying scientometric, legal and statistical analyses, confirm that energy poverty is a relatively nascent topic, with only 62 scientific articles on the region published since 1991. From this body of knowledge, we identify key differences in the geographies of energy poverty identified by different metrics, with energy services-based approaches generally indicating higher vulnerability within rural areas, while energy expenditure metrics point towards higher risk in urban areas. We also find a dominance of quantitative approaches that tend to use existing (and often limited) forms of survey data, and a relative absence of detailed qualitative research. As such, we argue there is an urgent need for transformative research and policy activities within Latin America and the Caribbean, in order to support access to clean, reliable, and affordable energy services for all.